„Bibliotekarz” 1919–1929–1939 – czasopismo nie tylko dla bibliotekarzy. Cz. III. Tematyka nie-bibliotekarska (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
Polish Library Association together with the Public Library of the Capital City of Warsaw edited in the years 1919, 1929–1939, a professional and popular journal for librarians with the titles: „Bibliotekarz” (1919, 1934–1939) and „Biuletyn Biblioteki Publicznej m.st. Warszawy” (1929–1933). The journal focused om librarianship. The journal’s pages were also open to non-librarian topics. „Bibliotekarz”, although focused on librarians, had ambitions that also concern other aspects, and their importance concerns various issues of knowledge represented in the library. This is also evidenced by bibliographic lists of books from various scientific disciplines. Special attention was paid to on the consequences of the humanities, social sciences and the effects on the pages of the magazine. As revealed by the detailed analysis, it is still the main source of information about librarianship in the Polish interwar period. Philosophical, sociological, literary, economic and user topics were discussed in detail. The content of the journal was analyzed, which made it possible to characterizing research in terms of thematic significance.